The multimorbidity association of metabolic syndrome and depression on type 2 diabetes: a general population cohort study in Southwest China - Cai, Yulan; Zhou, Shiyu; Fan, Shangheng; Yang, Yan; Tian, Kunming; Luo, Lei; Deng, Renli; Dai, Xingyu; Wang, Yiying; Zhu, Minglan; Liu, Tao (Frontiers in Endocrinology, 2024)
Background Metabolic syndrome(MetS) and depression are independently associated with type 2 diabetes (T2DM) risk. However, little is known about the combined effect of MetS and depression on the risk of T2DM. The present study aims to prospectively explore the impact of MetS and depression on T2DM susceptibility among the Chinese general population.Methods 6489 general population without T2DM adults in Southwest China were recruited from 2010 to 2012. Depression and MetS were prospectively assessed using a 9-item Patient Health Questionnaire(PHQ-9) and Guideline for the prevention and treatment of type 2 diabetes mellitus in China (2020 edition) (CDS2020) during 2016-2020, respectively. Modified Poisson regression models were conducted to estimate relative risk(RR) and 95% confidence intervals (95%CI) for independent and combined associations of MetS and depression with an incidence of T2DM.Results During a median follow-up of 6.6 years, 678 cases of T2DM were documented. Individuals with MetS were 1.33 times more likely to develop T2DM than those without MetS. The corresponding RR(95%CI) for depression with no depression was 1.45(1.22-1.72). Notably, compared with no MetS or depression, the multivariate-adjusted RR for a combined effect of MetS and depression on the risk of T2DM was 2.11(1.39-3.22). Moreover, an increased risk of T2DM was more apparent in those ≥ 60 years, males, and overweight.Conclusions Individuals with multimorbidity of MetS and depression are at a higher risk of T2DM compared with those with no MetS or depression.